East Java Basin Carbonate Reservoirs: Time Control on Reservoir Character - Darman, Herman; Abigail, Stevany; Lamba, Lisa Christi; Wulandari, Diah Retno; Ascaria, Alit; Prasetya, Lilik (Ikatan Ahli Geologi Indonesia, 2025)
The East Java Basin, a prolific back-arc basin in Indonesia, hosts significant hydrocarbon accumulations within Cenozoic carbonate reservoirs. This study explores the link between carbonate age, fossil assemblages, and reservoir characteristics. The oldest reservoir, the Ngimbang Formation, dominated by large foraminifera and interbedded shale, exhibits limited vertical growth potential. Conversely, the Oligo-Miocene Kujung Formation, rich in coral reefs, boasts the basin's highest hydrocarbon content. Pliocene Globigerina sands offer excellent reservoir quality due to both inter- and intra-granular porosity, but their distribution is restricted. This work analyzes the variations in reservoir properties (porosity and permeability) influenced by these distinct fossil assemblages across the formations. Additionally, comparisons of formation geometries and their impact on hydrocarbon trapping are addressed. By understanding these factors, the paper explores the potential for identifying hidden reservoirs within the basin for future exploration.